Effects of exclusive lease agreements on competition in the grocery retail sector in South Africa - Ngcakani, Mary Motlatji (University of the Witwatersrand, Johannesburg, 2023)
South Africa’s grocery retail sector is highly concentrated and dominated by five national supermarket chains utilising exclusive lease agreements (ELAs) with shopping mall developers to entrench and maintain their dominance. Exclusivity provisions in ELAs prevent small and emerging retailers from growing and penetrating shopping malls. This conduct has been the subject of several complaints to the Competition Commission, which initiated and conducted a grocery retail market inquiry (GRMI). This research report evaluated the effects of ELAs on competition in the grocery retail sector in South Africa. Competition is regulated by the Competition Act 89 of 1988. Therefore, the use of ELAs was critically analysed through the lens of sections 8(1)(b) and 8(1)(c) of the Competition Act, which prohibit the abuse of dominance. The research report highlighted that the use of ELAs negatively impacts competition in the grocery retail sector in South Africa. The paper argues that instead of initiating the GRMI, the Competition Commission could have utilised the abuse of dominance provisions of the Competition Act to achieve a more equitable outcome that furthers the objectives of the Competition Act.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Laws, University of the Witwatersrand, Johannesburg, 2023
Keywords: Effects of exclusive lease agreements on competition in the grocery retail sector in South Africa; Retail stores; Supermarket; Exclusive lease agreements (ELAs); Shopping; UCTD; SDG-8: Decent work and economic growth